2022
DOI: 10.1210/jendso/bvac017
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Sitagliptin and Spironolactone With Combination Therapy in Hospitalized Adults With COVID-19

Abstract: Background COVID-19 may cause respiratory distress syndrome and death. Treatment of COVID-19 to prevent complications remains a priority. Our investigation sought to determine whether combination of spironolactone and sitagliptin could reduce mortality for inpatient with SARS-CoV-2 infection. Methods This single blind, 4-arms, prospective randomized clinical trial was conducted at Shiraz and Bushehr University of Medical Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
0
22
0
3
Order By: Relevance
“…The proposed mechanisms could be the immunomodulatory functions (29), reduction of virus entry and diminishing viral replication. Therefore, the combination of DPP4 inhibitors and spironolactone could potentially improve the clinical outcomes better than each one alone (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanisms could be the immunomodulatory functions (29), reduction of virus entry and diminishing viral replication. Therefore, the combination of DPP4 inhibitors and spironolactone could potentially improve the clinical outcomes better than each one alone (36).…”
Section: Discussionmentioning
confidence: 99%
“…The Institutional Review Boards of the University of Kentucky, and Shiraz University of Medical Sciences approved the study. The current trial is registered as an addendum to the previous trial, which was conducted on the admitted patients (36). The authors confirm that all ongoing and related trials for these drugs are registered.…”
Section: Methodsmentioning
confidence: 99%
“…Despite a variety of mechanistic hypotheses, few investigations of either clinical efficacy or in vitro effect have been performed for spironolactone in COVID-19. A recent interventional study of spironolactone-sitagliptin combination therapy showed statistically non-significant improvements in clinical outcomes, including mortality, ICU admission, intubation rate, and end-organ damage, for patients on spironolactone (44). Another interventional trial showed no significant clinical improvements for COVID-19 patients on potassium canrenoate, a mineralocorticoid receptor antagonist similar to spironolactone (45).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many recent studies have investigated the antioxidant and anti-inflammatory effects of these inhibitors. 6 - 13 …”
Section: Introductionmentioning
confidence: 99%